A Facile Solvothermal Process to Synthesize MSnO3 (M = Sr, Mg) Nanoparticles Assisted by Microwave Irradiation - Sung Lim, Chang (Asian Journal of Chemistry, 2013)
MSnO3 (M = Sr, Mg) nanoparticles were synthesized successfully using a facile microwave solvothermal route followed by further heat-treatment. Well-crystallized SrSnO3 and MgSnO3 nanoparticles were formed after heat-treatment at 800 ºC for 3 h showing a fine and homogeneous morphology with particle sizes of 20-40 nm for SrSnO3 and 50-200 nm for MgSnO3. The synthesized SrSnO3 and MgSnO3 nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy and transmission electron microscopy.